Catalytic feasibility of Ce-doped LaCoO3 systems for chlorobenzene oxidation: An analysis of synthesis method - Acosta Perez, Hector (2021)
A family of Ce-doped LaCoO3 perovskites are presented as possible catalysts for Cl–VOCs elimination. These materials with different contents of Ce were obtained through the citrate and the reactive grinding methods. The insertion of Ce in the original perovskite structure favours the presence of Co2+/Co3+ and Ce3+/Ce4+ redox pairs and a higher content of oxygen vacancies that enhances the catalytic performance in chlorobenzene combustion based on differential kinetics studies. The family obtained by the grinding method presents a performance as high as that synthesized by citrate method. Thus, the reactive grinding is a feasible green chemistry alternative to obtain a catalyst with the same performance as that obtained from traditional methods. Finally, the stability of samples was evaluated under total combustion reaction conditions showing an excellent activity during 45 h time on stream.